Postharvest feed resource handling and utilization - Bezabih, Melkamu (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation in Media Training workshop on Livestock Feed and Forage Innovation. Addis Ababa, Ethiopia.